Fazna meja kovina/polprevodnik - Kovač, Janez (Vakuumist, 2001)
Electrical properties of metal/semiconductor junctions depend on caracteristics of the interface between materials. Methods for surface characterisation can be used to investigate model interfaces as a thin adsorbed layer of metal that can be complementary to the measurements of electrical characteristics (I-U, C-U). We present a study performed in order to improve the understanding of microocopic morphological effects during the formation and evolution of metal/semiconductor interfaces and electronic properties of these interfaces. For this purpose we studied the interaction between deposited Au thin films and interfaces Ag/Si(111) containing different morphological phases formed at elevated temperatures. By means of spatially resolved Si 2p, Ag 3d and Au 4f photoelectron spectra, obtained with the new photoelectron microscope at the Elettra synchrotron radiation facility, the composition and chemical status at interfaces were examined. The electronic properties of diffrent phases were deduced from the shift of the Si 2p and valence band spectra.
Keywords: fazne meje; kovine; polprevodniki; električne lastnosti; tanke plasti; interakcije; elektromigracija